Physics of semiconductor devices - Rudan, Massimo (Springer New York, 2015)
This ebook describes the basic physics of semiconductors, including the hierarchy of transport models, and connects the theory with the functioning of actual semiconductor devices. Details are worked out carefully and derived from the basic physics, while keeping the internal coherence of the concepts and explaining various levels of approximation. Examples are based on silicon due to its industrial importance. Several chapters are included that provide the reader with the quantum-mechanical concepts necessary for understanding the transport properties of crystals. The behavior of crystals incorporating a position-dependent impurity distribution is described, and the different hierarchical transport models for semiconductor devices are derived (from the Boltzmann transport equation to the hydrodynamic and drift-diffusion models). The transport models are then applied to a detailed description of the main semiconductor-device architectures (bipolar, MOS). The final chapters are devoted to the description of some basic fabrication steps, and to measuring methods for the semiconductor-device parameters.